2018
DOI: 10.1080/14756366.2018.1504041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cellular bioactivities of novel isoxazole derivatives incorporating an arylpiperazine moiety as anticancer agents

Abstract: In our endeavour towards the development of effective anticancer therapeutics, a novel series of isoxazole-piperazine hybrids were synthesized and evaluated for their cytotoxic activities against human liver (Huh7 and Mahlavu) and breast (MCF-7) cancer cell lines. Within series, compounds 5l-o showed the most potent cytotoxicity on all cell lines with IC50 values in the range of 0.3–3.7 μM. To explore the mechanistic aspects fundamental to the observed activity, further biological studies with 5m and 5o in liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Our finding, regarding the fact that the isoxazolic nucleus (for the CLD derivative) and the dimethoxylated aromatic nucleus (for the CLC derivative) generate the most active nanoparticles, is also sustained in the context in which the studies in this field have reported a naturally occurring diarylisoxazole derivative, as a new chemical tool with efficacy against breast cancer cells 22. In addition, in their study, Çalışkan et al [42] have synthesized new isoxazole-piperazine hybrids and analyzed their cytotoxic activities on human cancer cell lines. In this study, the isoxazole derivatives showed moderate to significant cytotoxicity on the used cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding, regarding the fact that the isoxazolic nucleus (for the CLD derivative) and the dimethoxylated aromatic nucleus (for the CLC derivative) generate the most active nanoparticles, is also sustained in the context in which the studies in this field have reported a naturally occurring diarylisoxazole derivative, as a new chemical tool with efficacy against breast cancer cells 22. In addition, in their study, Çalışkan et al [42] have synthesized new isoxazole-piperazine hybrids and analyzed their cytotoxic activities on human cancer cell lines. In this study, the isoxazole derivatives showed moderate to significant cytotoxicity on the used cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…[39] 4-Benzoyl-5-phenylamino-2,3-dihydrothiophene-2,3-dione (1) was obtained by careful addition of phenyl isothiocyanate (10 mmol) to ethyl 2,4-dioxo-4-phenylbutanoate (10 mmol) in KOH (10 mmol) and DMF (20 mL) with stirring for 24 hours at room temperature. [39] 4-Benzoyl-5-phenylamino-2,3-dihydrothiophene-2,3-dione (1) was obtained by careful addition of phenyl isothiocyanate (10 mmol) to ethyl 2,4-dioxo-4-phenylbutanoate (10 mmol) in KOH (10 mmol) and DMF (20 mL) with stirring for 24 hours at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis and characterization of compounds 17-31 and 32-46 has been published previously [9,11]. Chalcones (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) were prepared by Claisen-Schmidt condensation reaction (Scheme 1) in the presence of aqueous potassium hydroxide as a catalyst. The 1-(isoxazole-5-yl)ethanone (1) was condensed with substituted benzaldehyde (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) under basis conditions at room temperature for 24 h. The reaction was stopped by transferring the mixture on ice.…”
Section: Chemistrymentioning
confidence: 99%
“…Hence, we decided to screen our compounds for antibacterial, antifungal, antioxidant, and anticancer (prostrate cell line) activities. The target chalcones (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) and pyrazolines (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) were tested for their antimicrobial activities by serial tube dilution method against two types of bacterial and fungal strains (Tables 1 and 2). The bacterial strains used for the testing, including Gram-positive Staphylococcus aureus and Gram-negative Pseudomonas aeruginosa, whereas the fungal strains employed were Aspergillus niger and Candida tropicalis.…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 99%